Actions helping expressed or anticipated needs: Patients with advanced cancer and their family caregivers' experiences of specialist palliative home care teams. (9th October 2018) - Klarare, Anna; Rasmussen, Birgit H.; Fossum, Bjöörn; Hansson, Johan; Fürst, Carl Johan; Lundh Hagelin, Carina
Abstract: Patients with advanced cancer and family caregivers in palliative care face physical, psychological, social and existential challenges, much of the time home alone. Specialist palliative home care team services can be instrumental for sense of security in an uncertain situation. The aim of this study was to describe patients' and family caregivers' experiences of specialist palliative home care team actions that are identified by the participants as helping or hindering interventions. Six patients and seven family caregivers were interviewed using the enhanced critical incident technique. Ninety‐five critical incidents and wish list items were identified. Providing adequate resources, keeping promises and being reliable, and creating partnerships are actions by specialist palliative care teams that patients and family caregivers experienced as helping in meeting expressed or anticipated needs in patients and family caregivers. Being reliable and including patients and family caregivers in partnerships help to continue with daily life, even though death may be close. Unmet needs resulted in experiences of disrespect or violation of personal space/integrity.